Les entretiens dans la recherche et la formation pour le tutorat en ligne - Marco Cappellini; Marion Tellier; Isabelle Cros (Recherches en didactique des langues et des cultures, 2023)
In this paper, we focus on the epistemological issues surrounding the use of verbalisations in language didactics research. After a brief history of the introduction of these methods in language didactics, we question them in light of recent results in cognitive science. This leads us to formulate a proposal for training interviews based on stimulated-recall interviews and to consider that while the use of these tools for research may be problematic, it offers very promising possibilities for the professionalisation and training of trainers. We then propose a methodological framework for assessing the influence of interviews on the development of teaching, using an initial online tutoring training system as our field of study.